Working in new disability markets: A survey of Australia's disability workforce - Cortis, Natasha; Van Toorn, Georgia (UNSW Sydney, 2020)
This report provides information about the workforce delivering disability services and supports in the context of the National Disability Insurance Scheme (NDIS) in early 2020. The information comes from a national survey of disability workers (n=2341) which was designed to capture information from disability workers about the nature of their work and how it is changing, their experiences of working to support people with disability, and perceptions of the NDIS. The results provide comprehensive, contemporary evidence that values workers’ views and experiences and can be used to inform approaches to disability service provision in Australia, and the operation and regulation of the NDIS.